Lead (Pb) isotope signatures for silcrete sources from the Willandra Lakes region, Australia: A pilot study of a new method for provenancing silcrete artefacts. (February 2019) - Kurpiel, Rebekah; Pickering, Robyn; Maas, Roland; Stern, Nicola
Abstract: Silcrete was often used to make stone tools and the ubiquity of this material in the archaeological record has sparked considerable interest in developing techniques that can be used to trace its geographic origin. However, the highly variable physical and chemical properties of silcrete means that artefacts made from this raw material have proved difficult to provenance. This paper describes the use of Pb isotope analysis to characterize and differentiate silcrete sources in the Willandra Lakes region, a UNESCO World Heritage listed site in southeastern Australia. The sample collection strategy employed in the field has allowed Pb isotope variation both within and between the silcrete sources to be described. Pb isotope variation within each silcrete source does not exhibit spatial patterning, but Pb isotope signatures differ between silcrete sources in the Willandra Lakes region, and clear separation between more distant sources, is demonstrated. This represents a first step in being able to use isotope analysis to investigate how silcrete from different sources was used and how it was moved around the landscape. Highlights: Patterned variation in Pb isotope composition characterizes these silcrete sources. The variation is randomly distributed within sources but signatures differ between sources. The sources with the greatest geographic separation exhibit the greatest differences.